LncRNA PCBP1-AS1 suppresses cell growth in oral squamous cell carcinoma by targeting miR-34c-5p/ZFP36 axis: Role of PCBP1-AS1 in oral cancer - Shafiee allaf, Orkideh; Li, Wenhao; Zeng, Chongmai; Li, Peiru; Zhang, Yating; Xu, Yue; Bao, Baicheng (Cellular and Molecular Biology, 2024)
Oral squamous cell carcinoma (OSCC) is the most frequently diagnosed oral malignancy and poses a great threat to public health. According to bioinformatics analysis, long noncoding RNA PCBP1-AS1 is downregulated in OSCC. In this work, the functions and mechanism of PCBP1-AS1 in OSCC were further investigated. PCBP1-AS1 expression in OSCC cells was measured by quantitative polymerase chain reaction. Cell viability and proliferation were detected using CCK-8 assays and colony-forming assays. TUNEL assays as well as flow cytometry analyses were carried out to detect OSCC cell apoptosis. Binding relationship between PCBP1-AS1 and miR-34c-5p or that between miR-34c-5p and ZFP36 in OSCC cells was identified using RNA immunoprecipitation assays, RNA pulldown assays, and luciferase reporter assays. Experimental results revealed that PCBP1-AS1 was downregulated in OSCC cells. PCBP1-AS1 overexpression hampered cell proliferation and enhanced cell apoptosis in OSCC. PCBP1-AS1 interacted with miR-34c-5p in OSCC and negatively regulated miR-34c-5p. ZFP36 3’untranslated region was targeted by miR-34c-5p. PCBP1-AS1 positively regulated ZFP36 expression. ZFP36 silencing abrogated the suppressive impact of PCBP1-AS1 on OSCC cell growth. In summary, PCBP1-AS1 suppresses cell growth in OSCC by upregulating ZFP36 through interaction with miR-34c-5p.